The Amānah of Governance: Internal Control, Islamic Organizational Culture, and Fraud Risk Mitigation - Elex Sarmigi; Endah Sri Wahyuni (TSAQAFAH, 2025)
This study examines the relationships between the COSO Internal Control Framework, Islamic Organizational Culture (IOC), fraud prevention, and organizational performance in public sector institutions. Using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with a sample of 175 respondents, the findings reveal that COSO does not have a significant direct effect on either fraud prevention or organizational performance. In contrast, IOC demonstrates a strong and significant influence on both fraud prevention and performance. This result indicates that value-based cultural attributes rooted in Islamic principles—particularly amanah, sidq, and accountability—function as mechanisms that realize key maqāṣid al-Sharīʿah objectives, namely the preservation of wealth (hifẓ al-māl) through the prevention of fraud, and the preservation of faith (hifẓ al-dīn) by reinforcing ethical and religious compliance within organizational practices. The results further show that fraud prevention positively improves performance and mediates the relationship between IOC and performance, while COSO exhibits no mediating effect through fraud prevention. These findings refine Institutional Theory by demonstrating that in Islamic public-sector contexts, normative and cultural pillars (represented by IOC) possess stronger legitimizing power for shaping organizational behavior than purely regulatory or coercive structures (represented by COSO). Formal controls alone are insufficient without the support of deeply internalized ethical and religious values. Overall, the study highlights the importance of integrating Islamic ethical norms, cultural foundations, and fraud prevention mechanisms as practical embodiments of hifẓ al-māl to achieve more effective, accountable, and trustworthy governance.